Heavy Metal Removal From Semiconductor Industry Wastewater A Review On Ion Exchange Process Using Resin - Sabri, Nurul Arisya Shuhada (Universiti Sains Malaysia, 2021)
Due to a scarcity of surface water supply caused by declining water surface quality, groundwater is becoming an increasingly essential source of water. Many manufacturing firms in an industrialized country like Malaysia release their effluent into bodies of water that must be treated, increasing the demand for wastewater treatment. Ion exchange resin is one of the most successful ways for removing heavy metal ions from semiconductor industry wastewater, and it may be reused numerous times. The goal of this study was to use ion exchange resin as an adsorbent to remove typical heavy metals prevalent in semiconductor industry effluent. The results of a systematic literature study of thirty papers show the most common parameters to investigate are the effects of contact times ranging from 80 to 360 minutes, initial concentrations ranging from 0.2-3.0 g and resin doses ranging from 0.1-3.0 g. The pH of wastewater at 5 has already reached the equilibrium range of 83% to 97% according to the study. The far more typically used resins for removing heavy metals from semiconductor effluent and aqueous solutions are also compared and differentiated. Except for Lewatit CNP80 which has a carboxylic group while D401 and 732-Cr have high total capacity exchangers and the same functional group as sulphonic acid. Ion exchange kinetics are frequently pseudo first- order and pseudo second-order kinetics, where the data obtained indicates a correlation coefficient less than one for both ion exchange kinetics. Whereas ion exchange isotherms are frequently based on two primary isotherms, the Langmuir and Freundlich models with the highest R2 regression coefficient.